Dengue Virus Directly Stimulates Polyclonal B Cell Activation. - Arturo Ramon Vargas Correa; Ana Carolina Egypto Rosa Berbel; Michelle Premazzi Papa; Ana Theresa Silveira de Morais; Ligia Maria Torres Peçanha; Luciana Barros de Arruda (PLoS ONE)
Dengue infection is associated to vigorous inflammatory response, to a high frequency of activated B cells, and to increased levels of circulating cross-reactive antibodies. We investigated whether direct infection of B cells would promote activation by culturing primary human B lymphocytes from healthy donors with DENV in vitro. B cells were susceptible, but poorly permissive to infection. Even though, primary B cells cultured with DENV induced substantial IgM secretion, which is a hallmark of polyclonal B cell activation. Notably, DENV induced the activation of B cells obtained from either DENV immune or DENV naïve donors, suggesting that it was not dependent on DENV-specific secondary/memory response. B cell stimulation was dependent on activation of MAPK and CD81. B cells cultured with DENV also secreted IL-6 and presented increased expression of CD86 and HLA-DR, which might contribute to B lymphocyte co-stimulatory function. Indeed, PBMCs, but not isolated B cells, secreted high amounts of IgG upon DENV culture, suggesting that interaction with other cell types in vivo might promote Ig isotype switching and IgG secretion from different B cell clones. These findings suggest that activation signaling pathways triggered by DENV interaction with non-specific receptors on B cells might contribute to the exacerbated response observed in dengue patients.